Техніко-економічне обґрунтування доцільності використання адаптивного рульового керування колісного трактора - Журавель, Дмитро Павлович; Бондар, Андрій Миколайович; Zhuravel, Dmytro; Bondar, Andrii (Запоріжжя : ТДАТУ, 2024)
UA: В статті розглянуто питання техніко-економічного обґрунтування доцільності використання адаптивного рульового керування колісного трактора. Проаналізовані сучасні роботи, які пов’язані із визначенням ефективності впровадження науково-технічних рішень та обрані найбільш сучасні. В процесі проведення досліджень було встановлено, що запропонована система рульового керування з постійною чутливістю має високий рівень науково-технічного ефекту. При розрахунку терміну окупності додаткових капітальних вкладень було встановлено, що він становить 1,3 року, це є значно кращим терміном ніж рекомендовані нормативи, які розраховані на 7 років. Використання рульового керування транспортного засобу з постійною чутливістю дає можливість отримати річний економічний ефект в обсязі 161807,2 грн. EN: Powered wheeled tractors are currently widely used in all climate zones in approximately fifty transport, technological and agricultural operations. However, in operating conditions, all the capabilities of these wheeled tractors are not always used rationally. One of the main directions of increasing the productivity of tractors in agriculture is the maximum use of their traction and power properties. This is possible only when the working speeds of the power tool are increased. However, work at high speed modes leads to a deterioration in the stability of technological processes due to an increase in steering sensitivity, because with an increase in the speed of the machine-tractor unit, it is necessary to increase the gear ratio of the steering mechanism, and with a decrease in speed, accordingly, reduce it. To date, there is no such agricultural machinery, the steering of which would fully meet these requirements. Therefore, scientific work aimed at creating steering systems for agricultural machine-tractor units operating at high-speed modes and ensuring the adaptability of the steering gear ratio depending on the speed of its movement is relevant. The article deals with the issue of feasibility study of the feasibility of using adaptive steering on a wheeled tractor. Modern works related to determining the effectiveness of the implementation of scientific and technical solutions are analysed and the most modern ones are selected. During the research, it was established that the proposed steering system with constant sensitivity has a high level of scientific and technical effect. When calculating the payback period of additional capital investments, it was found that it is 1.3 years, which is a much better period than the recommended standards, which are calculated for 7 years. The use of vehicle steering with constant sensitivity makes it possible to obtain an annual economic effect in the amount of UAH 161807.2. The net discounted income from the use of modernized steering was also calculated and it was determined that it will amount to UAH 10,649.6 in the first year of use, and UAH 85455.3 in 7 years.
Feasibility study of the feasibility of using adaptive steering of a wheeled tractor
Keywords: колісний трактор; рульове керування; науково-технічний ефект; коефіцієнта ефективності інвестицій; експлуатаційні витрати; термін окупності; wheeled tractor; steering; scientific and technical effect; investment efficiency ratio; operating costs; payback period